Nonsteroidal anti-inflammatory drugs as a pharmacological alternative in Alzheimer's disease (Research, Society and Development, 2023)
Introduction: Inflammatory response in AD is characterized by the presence of activated microglia (the resident immunocompetent cells of the brain) in close association with neuritic plaques. Current evidence suggests that microglia are primarily involved in phagocytic activity and may be responsible for inducing additional neuronal damage by generating oxygen species and proteolytic enzymes. If anti-inflammatory drugs protect against the neurodegeneration seen in the brain of AD patients, then patients with a history of anti-inflammatory use should have a reduction in pathological changes in the brain and brain inflammation. Objective: to explain about the use of non-steroidal anti-inflammatory drugs as drug therapy for Alzheimer's disease. Results: Brain inflammation is believed to contribute to the pathological features of Alzheimer's disease (AD), and it has been postulated that anti-inflammatories protect against this tissue damage. However, one of the controversial factors regarding the use of non-steroidal anti-inflammatory drugs to reduce the risk of developing Alzheimer's disease is the toxicity associated with these drugs. Methodology: This is a systematic literature review with works searched in the following databases: National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Library Health Virtual (VHL) and EBSCO Information Services. Relevant sources inherent to the theme were analyzed, using as one of the main criteria the choice of current, original and international articles. A total of 12 scientific articles were available for review. Final considerations: Anti-inflammatory drugs have been suggested as a possible treatment for Alzheimer's disease (AD). The association of immune proteins and immunocompetent microglial cells with senile plaques (SP) in AD and normal aging suggests that these drugs may be able to modify the course of AD, either interfering with SP formation or suppressing inflammation.